Development of Powtoon Media on Natural Resources Material to Increase Learning Interest and Logical Thinking of Learners in Elementary School - Vina Yuniar; Nurdyansyah Nurdyansyah (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2023)
This study aims to develop animated videos that can help project images of various natural resources with technological advances. In the era of society 5.0, educators must be able to use more interesting learning methods. This audio-visual media will increase students' interest in learning. In addition, it is also to find out the feasibility and effectiveness of the results of developing PowToon-based animated videos. This study uses the Research and Development (RnD) method. This research model uses ADDIE, namely analysis, design, development, implementation, and evaluation. Data collection techniques used are questionnaires and tests in descriptive quantitative data. The media that will be used for learning is said to be valid by the three experts as evidenced by the results: (1) material experts have a validity percentage of 81 percent (2) media experts are 84 percent, (3) language experts are 75 percent. After being declared valid, the media was tested on class IV SDN Kalanganyar students. Based on the pre-test's t-test analysis, the average value is 60.0, and the post-test is 78.5. Because the value of sig. (2-tailed) or test 1 of 0.00, which means is less than or equal to 0.05, it can be concluded that Ho is rejected, and Ha is accepted. The conclusions that can be drawn from the results of this study indicate that there is a significant influence from animated video so that can increase interest in learning and logical thinking of fourth-grade students at SDN Kalanganyar.